Successful resection of giant abdominal hemophilic pseudotumor: Surgical treatment and follow-up outcomes in one single center - Liu, Shuzhong (Medicine (Baltimore), 2019)
Giant abdominal hemophilic pseudotumor is exceedingly rare, thus may bring great challenges to the timely and proper diagnosis and treatment of clinicians. The only definitive management is complete removal of the abdominal hemophilic pseudotumor. The objective of this article is to report surgical treatment and follow-up outcomes of three unusual cases with giant abdominal hemophilic pseudotumor. We describe 3 patients with giant hemophilic pseudotumor involving the abdomen who were successfully treated with tumor resection. On presentation to our institution, the patients all had signs of giant cystic lesions in abdomen, and the patients’ most outstanding complaints were aggravated abdominal pain. All of three patients underwent complete excision of abdominal hemophilic pseudotumor. The patients showed adequate pain relief compared with the previous status. Surgical resection is the most effective treatment option for patients with giant abdominal hemophilic pseudotumor who can undergo appropriate surgical treatment. This represents a safe and reasonable approach to sustainably relieve pain and other symptoms with giant hemophilic pseudotumor in the abdomen. Perioperative coagulation factor replacement therapy is also of great significance in reducing the risks and complications.